The Relationship Between Company Size, KAP Reputation, and Auditor Opinion on Audit Delay Moderated by Legal Compliance - Purwanti, Ni Kade Dian; Latrini, Made Yenni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to examine the relationship between company size, KAP reputation, auditor opinion, and legal compliance on audit delay. The research population of food and beverage companies listed on the IDX for the period 2018-2023 used a nonprobability sampling method with purposive sampling technique, which resulted in 114 observations. Using the Moderated Regressions Analysis (MRA) technique using SPSS 25 software. The results showed that company size has a positive relationship to audit delay, KAP reputation has no relationship to audit delay, and auditor opinion has a negative relationship to audit delay. In addition, legal compliance is unable to moderate the relationship between company size and audit delay, legal compliance is unable to moderate the relationship between KAP reputation and audit delay, and legal compliance is able to moderate the relationship between auditor opinion and audit delay.